Making an IMPACT on emergency department flow: improving patient processing assisted by consultant at triage. Issue 5 (25th August 2004) - Terris, J; Leman, P; O'Connor, N; Wood, R
Abstract : Objectives: To assess whether initial patient consult by senior clinicians reduces numbers of patients waiting to be seen as an indirect measure of waiting time throughout the emergency department (ED). Methods: An emergency medicine consultant and a senior ED nurse (G or F grade), known as the IMPACT team, staffed the triage area for four periods of four hours per week, Monday to Friday between 9 am to 5 pm for three months between December 2001 and February 2002 when staffing levels permitted. Patients normally triaged by a nurse in this area instead had an early consultation with the IMPACT team. Data were collected prospectively on all patients seen by the IMPACT team. The number of patients waiting to be seen (for triage, in majors and in minors) was assessed every two hours during the IMPACT sessions and at corresponding times when no IMPACT team was operational. Results: There was an overall reduction in the number of patients waiting to be seen in the department from 18.3 to 5.5 (p<0.0001) at formal two hourly assessments. The largest difference was seen in minors. Of the patients seen at triage by the IMPACT team, 48.9% were discharged home immediately after assessment and treatment. With the IMPACT team present, no patient waited more than four hours for initial clinical consult. Conclusions: By using a senior clinical team for initial patient consultation, the numbers of patients waiting fell dramatically throughout the ED. Many patients can be effectively treated and discharged after initial consult by the IMPACT team.